Untargeted metabolomics unveils metabolic biomarkers in HFpEF - Duan, Dongqin; Abudurexiti, Muyashaer; Abuduhalike, Refukaiti; Aimaier, Salamaiti; Mahemuti, Ailiman (Frontiers in Molecular Biosciences, 2025)
BackgroundHeart failure with preserved ejection fraction (HFpEF) is a complex condition linked to metabolic disturbances. This study aimed to identify plasma metabolic signatures in HFpEF patients using untargeted metabolomic profiling.MethodsWe analyzed data from 30 HFpEF patients and 30 matched healthy controls. Untargeted metabolomic profiling via UHPLC-MS/MS was conducted on venous blood to identify metabolic differences. Initial analyses included principal component analysis (PCA), partial least squares-discriminant analysis (PLS-DA), and hierarchical clustering to detect differing compound groups. Receiver operating characteristic (ROC) curve analysis and pathway enrichment were performed to identify dysregulated genes. Finally, enzyme-linked immunosorbent assay (ELlSA) was used to validate the serum levels of selected metabolites.ResultsA total of 124 significantly different metabolites were identified (VIP >1.0, FC > 1.2 or <0.833, P < 0.05). Lipids and lipid-like molecules were notably altered in HFpEF patients. KEGG enrichment analysis indicated these metabolites were primarily involved in tryptophan metabolism. Hierarchical clustering showed distinct compound levels between groups. ROC curve analysis revealed PC 18:1-20:5 (AUC: 0.833) and PC 18:1-18:1 (AUC: 0.824) as key metabolites. ELlSA validation confirmed that serum Kynurenine and IAA levels were significantly elevated in HFpEF patients compared to HCs (p < 0.05).